Idioma inglés y su influencia en los procesos comerciales - Fajardo Vera, Sonia Cecibel (2019)
The present case of study tries to make known the influence that the English Language has in the commercial processes of the Importadora Servirepuestos Lozada; This study show, the different shortcomings that the company study's object presents, regarding the competencies that the staff must have in relation to the English language, that involve sustained business development are disclosed. In this case of study, descriptive research is used, since the characteristics of the research variable are described; The method used is the inductive, to obtain the information that supports the development the case of study, the interview technique has also been used, supported by a questionnaire with open questions addressed to the import analyst of the company where the case The results obtained in the specific investigation that none of the collaborators dominate the English language, that represents a significant weakness to the company, owing to the characteristics of the business and the stage in which it carries out commercial activities; This has caused the company not to have the planned growth in business objectives. The conclusions reached in the investigation is that the English Language is indispensable for the Importadora Servirepuestos Lozada, therefore, by virtue of this, it needs to make pertinent corrections to improve the actual situation of the organization